Beyond the Iron Curtain: The emergence and causation of the Green movement in the USSR - Caspell, James (2007)
Abstract: The last decade of the Soviet Union witnessed unprecedented sociological and political change following the advent of Mikhail Gorbechev’s policies of glasnost and perestroika. Shifting tectonic plates of political opportunities provided the space for social movements to emerge that were critical of the status quo for the first time. The birth of political toleration allowed public acknowledgement that Soviet industrialisation had led to widespread environmental degradation and catastrophe – and an environmental movement emerged which opposed it